Clinical Time Features and Chest Imaging of 85 Patients With COVID-19 in Zhuhai, China - Liu, Zhuobing; Ding, Li; Chen, Gongqi; Zhao, Chaohui; Luo, Xiaoqing; Li, Xinghua; Luo, Wentao; Xia, Jinyu; Liu, Xi (Frontiers in Medicine, 2020)
Background: An outbreak of SARS-CoV-2 infections began in Wuhan, China and quickly spread to the entire country. We sought to delineate the time features of clinical symptoms, virological conversion, and chest radiological abnormalities in individuals infected with this virus in Zhuhai, China. Methods: In this retrospective study, we assessed 85 confirmed cases of COVID-19 in the Fifth Hospital of Sun Yat-sen University, Zhuhai from 17 January to 11 February 2020. Outcomes were followed up until 24 February 2020. Results: The median age of the 85 patients with COVID-19 was 43 years (range, 1–80); 56.5% (48/85) were female. The median time from the last known contact to the first SARS-CoV-2 positive test result was 8 days (0–18). The time to throat swab negativity for SARS-CoV-2 ranged from 5 to 36 days after illness onset. Patients with abnormal chest imaging findings on admission were older than those with normal imaging findings (median age, 50 [3–80] vs. 37 [1–69], P=0.031). Among patients with lung changes on admission, the risk of lesions was 13.8 times greater in the left lower lobe than in the right middle lobe. Most lung lesions appeared within 2 weeks of onset (median 4–5 days. The overall rates of lesions in the right upper/middle/lower lobe and left upper/lower lobe were 47.1%, 30.6%, 62.4%, and 49.4% and 63.5% respectively. Conclusions: The incubation period of SARS-CoV-2 may be longer than 14 days; thus, medical surveillance after contact is required for longer than this. The predominant sites of lung lesions are both lower lungs, whereas the lowest risk region is the right middle lobe.